Evidenciação contábil: uma análise das entidades mantenedoras das universidades brasileiras de ensino privado sem fins lucrativos - Pereira, Fernando Andrade (Universidade do Vale do Rio dos Sinos, 2012)
This study aimed to analyze the financial statements of entities that maintains nonprofit private universities in Brazil in accordance with accounting standards and applicable law. The theoretical framework used was based on the concept and characteristics higher education in Brazilian educational system, in legal and administrative organization of the entities that maintains educational institutions, in accounting disclosure and the content presented in the financial statements. The methodological framing took into account the qualitative and quantitative study with the use of documental research and help of statistical tools for analysis and data processing. The sample gathers published accounting statements of the financial year 2010 from 43 institutions in four Brazilian regions, being 24 civil associations and 19 foundations under private law. The results reveal that the associations maintain better conformity degrees in five of the seven analyzed items, presenting a general degree of 79% against 70% of the foundations, while the general degree of conformity of the study was of 75%. In the analysis by region, it was found that the educational institutions in the Southeast had higher levels of compliance in relation to other federal regions. The entities in the southern region were those that presented worst level of compliance in relation same as that indicated in legislation and standards for disclosure of accounting reports. Complementing studying, compliance levels were contrasted with gross income and economic indicators and financial of institutions allowing affirms that the institutions that disclose best are also those with higher income. The current ratio was the only economic-financial indicator that presented significant relation with the conformity levels.
Keywords: Evidenciação contábil; Universidades privadas; Ensino superior; Accounting disclosure; Private universities; Higher education; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis